2018
DOI: 10.2147/ott.s170392
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the autophagy in bone marrow stromal cells overcomes resistance to vorinostat in chronic lymphocytic leukemia

Abstract: BackgroundThe bone marrow microenvironment constitutes a sanctuary for leukemia cells. Recent evidence indicates that environment-mediated drug resistance arises from a reciprocal influence between tumor cells and the surrounding stroma. The present study aimed to investigate the effect of chronic lymphocytic leukemia (CLL) cells on the metabolism of bone marrow stroma, to determine the role of this metabolic change in the stroma in vorinostat resistance of CLL cells, and thus to assess a novel strategy to tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 68 publications
(84 reference statements)
0
16
0
Order By: Relevance
“…e autophagy-related protein expression also confirmed that the molecular mechanism is through inhibition of Akt/mTOR signaling. Interestingly, vorinostat or bendamustine alone failed to induce autophagy [29,46], thus suggesting that the induction of autophagy is a special trait of NL-101. Generally speaking, Akt needs phosphorylation of threonine phosphorylation site (thr308) or serine phosphorylation site (ser473) to regulate cell's function.…”
Section: Discussionmentioning
confidence: 99%
“…e autophagy-related protein expression also confirmed that the molecular mechanism is through inhibition of Akt/mTOR signaling. Interestingly, vorinostat or bendamustine alone failed to induce autophagy [29,46], thus suggesting that the induction of autophagy is a special trait of NL-101. Generally speaking, Akt needs phosphorylation of threonine phosphorylation site (thr308) or serine phosphorylation site (ser473) to regulate cell's function.…”
Section: Discussionmentioning
confidence: 99%
“…Leukemic cells can also relieve oxidative injury by interacting with the leukemia niche. Ding et al 74 reported that H 2 O 2 generated by chronic lymphocytic leukemia (CLL) cells under vorinostat treatment was transferred to the surrounding stromal cells and drove autophagy, mitophagy, and glycolysis, resulting in the local production of high-energy mitochondrial fuels, which were then taken up by CLL cells to be effectively utilized through mitochondrial oxidative phosphorylation to enable more ATP production (Fig. 2).…”
Section: Targeting Ros In Treatment For Leukemiamentioning
confidence: 99%
“…Mitochondrial respiration in whole cells was measured by an oxygen consumption assay, as described. 27 Following incubating with 1.5 mM Hcy for 20 hours, HUVECs were resuspended in 1 mL of fresh culture medium pre-equilibrated with 21% oxygen at 37°C, followed by applying the cells to the sealed respiration chamber of a Clark-type oxygen measuring system (Oxytherm; Hansatech Instruments, Cambridge, UK) with constant stirring.…”
Section: Mitochondrial Respiration Activitymentioning
confidence: 99%
“…29 Following incubating with 1.5 mM Hcy for 20 hours, HUVECs were labeled with 50 nM NAO for 15 min and analyzed using flow cytometry, as previously described. 27 A cytochrome c release kit (EMD Millipore, San Diego, CA, USA) and caspase 3 activation assay kit (BD Biosciences, San Jose, CA, USA) were used to measure the loss of mitochondrial cytochrome c and the levels of activated caspase 3, according to the manufacturer's instructions. Rhodamine 123 (Invitrogen Life Technologies) was used to evaluate mitochondrial transmembrane potential.…”
Section: Analysis Of Mitochondrial Oxidative Damage Cytochrome C Relmentioning
confidence: 99%
See 1 more Smart Citation